Multifunctional Furniture: Accompanying and Creating Child-Friendly Furniture: Furnitur Multifungsi: Pendampingan dan Pembuatan Furnitur Ramah Anak - Khairuni, Zhilli Izzadati; Zulkifli Matondang; Peny Husna Handayani; Liana Atika; Sarra Rahmadani (Universitas Lancang Kuning, 2024)
Farhanny khair daycare and preschool is a daycare place for children, As for the rest of daycare, this place is a home typology dwelling that is used as a daycare with additional activities as a learning / child play for the age of 2-5. In the condition of typology home buildings that are made into daycare and study and play, According to observation of some areas of unmaximized space meets the needs of motion space in children. Although this daycare location has space limitations but managers and teachers maximized the teaching system and management as well as comfort, hygiene, The safety of this daycare place is fine. That potential makes Farhany khair daycare and preschool entrusted parents to daycare while parents worked from 2018 to today. Based on the results of the situation analysis done by a team a proposer, So a team a proposer is trying to minimize the problems that are happening in child space and maximize the potentials that farhany khaanir daycare and preschool to make this daycare even better, and it can be beneficial for teachers and parents. The solution offered by a team a proposer is knowledge in the design of space within the scope of interior design according to the needs of young children so that existing space can be maximized into a playspace and study for children of daycare.In addition to knowledge of interior design the follower team also makes an innovation product a multifunctional shelf of children to be used by daycare as a means of supporting activity in that place